The Influence of Noodle Made from a Mixture of Moringa Leaf Powder and Wheat Flour on Consumer Preference Levels - Larasati, Sri (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Ampat Yogyakarta, 2023)
We find many kelor leaves in rural areas that have many benefits when collected and this is much unknown to the community, therefore to better introduce kelor Leaves, researchers try to make kelor Leaves become one of the mixed ingredients in making noodles by making powder after drying kelor leaves first and then grinding it by blending. The use of kelor leaf powder as the main mixture of noodles is carried out as an effort to create healthy noodle variants. So, the study entitled The Effect of Noodles Made from a Mixture of kelor Leaf Powder and Wheat Flour on the Level of Consumer Preferences. The purpose of this research is to determine the effect of kelor leaf powder related to its use in the main mixture of noodle dough on the level of consumer preference judging from taste, aroma, texture, color. This research is an experimental research using hedonic test as a method for panelists to give their assessment with. Data collection techniques through questionnaires. The data analysis method used by researchers in this study is the ftriedman test. From the results of the hypothesis test proposed for aspects of Taste, Aromo and Color using the ftriedman test rejected which means that there is a significant influence on the use of a mixture of kelor leaf powder and wheat as a basic ingredient, only the Texture aspect is accepted which means that the Texture aspect is the same as noodles in general Overall, the results of the hypothesis test proposed proved that there was an influence on the use of a mixture of kelor leaf powder in the basic ingredients of nemun noodles, so that noodles that use a mixture of kelor leaf powder are preferred by consumers